Smell and Taste in Severe CoViD-19: Self-Reported vs. Testing - Mazzatenta, Andrea; Neri, Giampiero; D'Ardes, Damiano; De Luca, Carlo; Marinari, Stefano; Porreca, Ettore; Cipollone, Francesco; Vecchiet, Jacopo; Falcicchia, Chiara; Panichi, Vincenzo; Origlia, Nicola; Di Giulio, Camillo (Frontiers in Medicine, 2020)
One of the most striking reported symptoms in CoViD-19 is loss of smell and taste. The frequency of these impairments and their specificity as a potential central nervous system function biomarker are of great interest as a diagnostic clue for CoViD-19 infection as opposed to other similar symptomatologic diseases and because of their implication in viral pathogenesis. Here severe CoViD-19 was investigated by comparing self-report vs. testing of smell and taste, thus the objective severity of olfactory impairment and their possible correlation with other symptoms. Because a significant discrepancy between smell and taste testing vs. self-report results (p < 0.001) emerges in our result, we performed a statistical analysis highlighting disagreement among normosmia (p < 0.05), hyposmia, severe hyposmia, and anosmia (p < 0.001) and, in hypogeusia and severe hypogeusia, while no differences are observed in normogeusia and ageusia. Therefore, we analyzed the olfactory threshold by an objective test revealing the distribution of hyposmic (34%), severe hyposmic (48%), and anosmic (13%) patients in severe CoViD-19. In severe CoViD-19 patients, taste is lost in 4.3% of normosmic individuals, 31.9% of hyposmic individuals, 46.8% of severe hyposmic individuals, and 17% of anosmic individuals. Moreover, 95% of 100 CoViD-19 patients objectively tested were affected by smell dysfunction, while 47% were affected by taste dysfunction. Furthermore, analysis by objective testing also highlighted that the severity of smell dysfunction in CoViD-19 subjects did not correlate with age and sex. In conclusion, we report by objective testing that the majority of CoViD-19 patients report severe anosmia, that most of the subjects have olfactory impairment rather than taste impairment, and, finally, that the olfactory impairment correlate with symptom onset and hospitalization (p < 0.05). Patients who exhibit severe olfactory impairment had been hospitalized for about a week from symptom onset; double time has taken place in subjects with normosmia. Our results may be limited by the relatively small number of study participants, but these suggest by objective testing that hyposmia, severe hyposmia, and anosmia may relate directly to infection severity and neurological damage. The smell test assessment could be a potential screening symptom that might contribute to the decision to test suspected cases or guide quarantine instructions, further therapeutic approach, and evaluation of neurological damage.